Cognate arguments and the Transitivity Requirement in the history of English - Lavidas, Nikolaos (Lingua Posnaniensis, 2014)
Starting with the Transitivity Requirement hypothesis [the direct object counterpart of Extended Projection P rinciple (EPP)], we examine the development of cognate objects and cognate subjects in English. We show that English extended the range of both cognate objects - which are now also possible with activity/event nouns - and cognate subjects - cognate subjects became an option for impersonal verbs. However, we argue that a correlation between the development of cognate arguments and the changes in null arguments should be excluded, whereas the development of the cognate arguments appears to be related to aspectual changes.